Education on the “Sifat Dua Puluh of Allah” in the Book Fawakih al-Janani by Al-Haj Abdul Rashid - Sri Hartati Adiningsih; Qanithah Fairus Azzahrah (Riviera Publishing, 2026)
This study analyzes Aqidah education on the